A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes: Heptapteridae) from the Orinoco River basin - Cortés-Hernández, Miguel Ángel; Donascimiento, Carlos; Ramírez-Gil, Hernando (Zootaxa, 2020)
A new species of Pimelodella is described from western Andean tributaries of the Orinoco River basin. The new species differs from all congeners by a unique set of characters that includes long maxillary barbel, surpassing the dorsal lobe of the caudal fin; relatively short adipose fin (32.8–36.4 of SL); 40–42 total vertebrae; posterior margin of pectoral-fin spine with 12–18 retrorse dentations along basal two thirds; laterosensory canal foramina of dentary and preopercle large and externally conspicuous; a brown faint and narrow midlateral stripe extending from the pseudotympanum, fading posteriorly along the caudal peduncle, and ending as a spot at the caudal-fin base; and dorsal-fin base darkly pigmented, from spinelet to posteriormost interradial membrane. Taxonomic status of P. pallida and presence of P. cruxenti in Colombia are also discussed.